State and Nation in Nineteenth Century International Political Theory: The Constitutional Framework and Evolution of International Relations in the Nineteenth Century (Journal of Advances and Scholarly Researches in Allied Education, 2021)
International relations, which are basically a societas of states, are examined in this chapterfrom the perspective of their constitutional framework. It examines the function of global bodies, NGOs,transnational networks, and human rights in such a world. It looks at the difference between aninternational system and a global society, the importance of political principles in international law, andthe relationship between prudential and procedural associations. At a tremendous cost to human life,imperial governments spread Western military technology and administration throughout the globe bymeans of blood and iron, triggering political reforms and modernisation even in the most venerable ofold empires. The European powers' overseas empires were broken by the combined consequences ofthe two World Wars, prompting the Europeans to retreat from Africa and Asia and give birth to dozens ofnew independent nations, the vast majority of which are now members of the United Nations.